Relations between preschooler social competence and coping tactics during resource‐based conflicts - Nichols, O.; Vaughn, B. E.; Coppola, G.; Shin, N.; Monteiro, L.; Krzysik, L. (Social Development, 2020)
Although peer conflict is a common event in preschool classrooms, few studies have examined relations between coping with peer conflict and social competence (SC) in preschool samples. In this study, 166 preschoolers (95 male) were observed during dyadic play episodes designed to induce a resource-based conflict. Coping tactics were coded using Zimmer-Gembeck and Skinner’s (2011) taxonomy and were evaluated in relation to indicators of SC assessed using direct observations and sociometric interviews. On average, the dyadic play episodes elicited 4.19 conflict events per partner, with children’s most common tactics being verbal assertion (29% of all conflict events) and physical assertion (17%). Preschoolers’ coping tactics showed moderate correspondence with current developmental taxonomies and regression analyses with SC were partly consistent with studies of older children. Cooperative tactics reflected higher levels of SC, particularly for boys, and failure to cope with the dilemma reflected lower levels of social competence. In this sample, the use of disengaged tactics was not associated with SC and only a few differences in coping tactic use were associated with the gender composition of the dyad. Results suggest coping tactics during resource-based conflicts at the preschool age are associated with measures of social competence and, with slight adjustments, map onto developmental frameworks.